Technical, tactical and spatial indicators related to goal scoring in European elite soccer - González-Ródenas, J.; López-Bondia, I.; Aranda-Malavés, R.; Tudela Desantes, A.; Sanz-Ramirez, E.; Aranda Malaves, R. (Journal of Human Sport & Exercise, 2020)
The aim of this study was to describe the technical, tactical and spatial indicators related to goal scoring in elite European soccer, considering the type of defence and the positioning of the opponent. For the analysis, 8 tactical dimensions related to the final actions in 380 sequences that led to goal during the UEFA Champions League were evaluated by observational methodology. 75.9% of the goals were scored from open play and 24.1% were scored from set pieces. Collective actions produced 51.6% of the total goals while individual actions produced 10.5% of goals. Regarding the penultimate action, crosses were more frequent against organized defences, while passes in behind the defence, or actions as dribbling or running with the ball had a greater percentage of goals against circumstantial defences (Chi2=37.027; p>0.001). Besides, greater utilization of wide invasive spaces (70.2%) was observed to assist against organized defences, while this percentage was 53.1% (Chi2=5.501; p=0.015) against circumstantial defences. For the last action, 70.1% of the goals were scored by using only one contact to the ball in organized defences but 46.6% in circumstantial defences (Chi2=26.521; p>0.001). The technical and tactical actions that achieve goal and their spatial characteristics are related to the type of defence used by the opposing team.